(untitled) (Iranian Journal of Kidney Diseases, 2013)
Introduction. Increased oxidative stress, inflammation, and malnutrition are present in hemodialysis patients and these factors exacerbate cardiovascular comorbidities. Vitamin E and α-lipoic acid (ALA) may have a protective role against cardiovascular disease risk factors via anti-oxidative and anti-inflammatory properties. The aim of this study was to evaluate the effect of ALA and vitamin E administration (alone or combined) on hemodialysis-induced stress oxidation, inflammation, and malnutrition. Materials and Methods. In a randomized placebo-controlled trial, we examined the effects of 2-month supplementation by vitamin E and ALA (alone or combined) on biomarkers of lipid peroxidation (malondialdehyde), inflammation (high-sensitivity C-Reactive protein and interleukin-6), and malnutrition (Subjective Global Assessment and body mass index) in 85 hemodialysis patients receiving ALA (600 mg), vitamin E (400 IU), ALA and vitamin E, and placebo. Results. After supplementation, no significant changes were observed in malondialdehyde level; however, there was a decrease in the ALA and vitamin E group during the period of the study. Also, a nonsignificant decrease was seen in the high-sensitivity C-Reactive protein concentration of the interventional groups. Supplementation of vitamin E with and without ALA significantly reduced interleukin-6 concentration. A significant improvement was observed in malnutrition status of all groups. Conclusions. Vitamin E and ALA supplementation, especially their combination, might improve inflammation and malnutrition status, which suggest it as a potential preventive strategy against CVD among end-stage renal disease patients.